Diseño conceptual de una planta piloto para el proceso de refinación de aceite crudo para el uso alimenticio (2017)
This document is the final report of the degree work entitled which has as its general objective to conceptually design a pilot plant for the palm oil refining process raw. Initially a sample of vegetable waste was diagnosed from transport tanks in the department of Meta, which was taken to the laboratories Colompack and Nutrianalisis S.A. to perform the physicochemical analyzes, which were compared with the characteristics of an industrial crude oil, such as humidity percentage, peroxide index, iodine index, acid number, saponification index and refractive index, thus concluding the need of a refining process. Subsequently, a bibliographic review of the types of vegetable oil refining at the industrial level was carried out. Two of the main ones were compared and the physical refining was selected which is better suited to make it at the laboratory level, I agree with the acidity index and content of unsaponifiable matter that were identified in the oil. Therefore, this process was carried out and the oil was characterized again, comparing with the resolution 2154, which indicates the characteristics that an oil must fulfill in order to be suitable for consumption, all parameters were not complied with, This raised a series of recommendations to improve refining.